(untitled) (Cardiovascular Journal, 2023)
Cardiac rehabilitation (CR) is a program that aims to improve the cardiovascular health of patients with coronary artery disease (CAD) through a multidisciplinary approach. CR typically includes exercise training, risk factor modification, psychosocial support, and education. Studies have shown that CR can improve exercise capacity, reduce angina symptoms, enhance overall quality of life, and reduce the risk of recurrent cardiovascular events. Despite the benefits of CR, adherence remains a challenge, and many patients with CAD do not participate in these programs. Strategies to improve adherence to CR include patient education, personalized goal setting, motivational interviewing, and peer support. Encouraging and supporting patients with CAD to participate in CR programs is crucial for the secondary prevention and long-term management of their condition. While CR programs are effective, access to these programs may be limited for some patients, particularly those in underserved communities or rural areas. Tele-rehabilitation, which uses technology to provide remote delivery of CR services, has shown promise in increasing access to CR for patients who may not have access to traditional in-person programs. Overall, CR is a vital component of the management of CAD, and its benefits extend beyond cardiovascular health to include improvements in overall quality of life. It is important to raise awareness about the importance of CR and to work towards increasing access to these programs for all patients with CAD. Cardiovasc j 2023; 16(1): 40-46